Peningkatan Kapabilitas Siswa Sekolah Dalam Belajar dan Penerapan IPTEK - Alis Nurhalimah; Bayu Andrea Pramayuda; Cahya Trika; Rizki Virgiawan; Teofilus Ardian Hopemam (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2023)
This community service has been carried out from August to September 2022 in Cikahuripan Village, Cisolok District, Sukabumi Regency. Some of the main problems in Cikahuripan Village are not yet optimal ability to use computer technology, public awareness about the importance of technology already exists but this only focuses on cellphone technology not on larger technology. This service aims to increase public awareness of the importance of mastery in the use of computer technology. The service is carried out in the form of a seminar with the title